Partisanship, Fiscal Transfers, and Social Spending in Korea: The Politics of Partial Decentralization - Ha, Eunyoung; Lee, Dong Wook (Journal of East Asian studies, 2022)
In the last three decades, many Asian democracies have decentralized their political systems to promote the democratic, equal, and efficient distribution of national resources across regions. Nonetheless, most of these countries, including South Korea, are still in a stage of “partial fiscal decentralization,” in which locally elected officials have spending authority, while a significant portion of their financing relies on transfers from the central government. This article argues that the decentralized distribution is significantly influenced by the partisan interests of central and local governments. The central government transfers more funds to local governments that their co-partisans govern, and local incumbents follow partisan policy priorities to obtain the allocation of available fiscal resources. This argument is strongly supported by the empirical analysis of subsidy transfers and regional social expenditures in South Korea from 2002 to 2015. First, we find that the central government in Korea transfers larger subsidies to politically aligned regions. Second, regional governments with larger subsidy transfers have higher levels of social expenditures. Third, governors or mayors affiliated with a progressive party spend significantly more on social welfare and education than do those affiliated with a conservative party.